The state and the ways of scientific and applied risk-diagnostic’s base’s development - A. M. Medvedeva; A. V. Palbin (Путеводитель предпринимателя, 2020)
In the article the analysis of risk-diagnosis’s methods the most widely represented in the scientific and applied materials for risk management is performed. Additionally the recommendations for building the most complete and appropriate list of entrepreneurial company’s risks are made.